2002
DOI: 10.1046/j.1440-6055.2002.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Hippodamia variegata (Goeze) (Coleoptera: Coccinellidae), a predacious ladybird new in Australia

Abstract: The originally Palaearctic but now widespread coccinellid Hippodamia variegata was recorded for the first time in Australia at Gatton, Queensland, in November 2000 . Since then, it has been recorded preying on 12 different aphid species and a psyllid, on a variety of crops, weeds and ornamental plants.Within a year of its discovery, it had been recorded within a distance of 800 km north and south and 500 km west of the original collection point. Collection and observation records are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 6 publications
0
46
0
2
Order By: Relevance
“…H. variegata originated in the Palearctic region (Gordon 1987) and is a widespread predator of aphids in many parts of the world (Franzmann 2002). This species is considered the most important natural enemy of aphids in many countries, including Bulgaria, Ukraine, Italy, India, and Turkmenistan (Kontodimas and Stathas 2005).…”
Section: Introductionmentioning
confidence: 99%
“…H. variegata originated in the Palearctic region (Gordon 1987) and is a widespread predator of aphids in many parts of the world (Franzmann 2002). This species is considered the most important natural enemy of aphids in many countries, including Bulgaria, Ukraine, Italy, India, and Turkmenistan (Kontodimas and Stathas 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hippodamia variegata (Goeze) (Coleoptera: Coccinellidae) sudah dilaporkan sebagai predator penting aphis pada tanaman cabai di Bulgaria, tanaman jagung di Ukraina, tanaman semak-semak di Italia, tanaman gandum di India serta pada tanaman kapas di Turmenistan (Kontodimas et al 2003), juga sudah dilaporkan memangsa 19 spesies aphis di Turki (Aslan & Uygun 2005) dan 12 spesies aphis dan kutu loncat pada tanaman pertanian, gulma dan tanaman hias di Australia (Franzmann 2002). Di India dan Vietnam pengendalian Aphis gossypii (Glover) (Homoptera: Aphididae) dan Myzus persicae (Sulzer) (Homoptera: Aphididae) dilakukan dengan memanfaatkan Lemnia biplagiata (Swartz) (Coleoptera: Coccinellidae) yang diintroduksi dari China dan sudah berlangsung sejak tahun 1990 (Tsai 1998).…”
Section: Pendahuluanunclassified
“…Predators obtained were Hippodamia variegata (Goeze), Oenopia conglobata (L.), Scymnus interruptus (Goeze), Scymnus mediterraneus Khnzorian, Stethorus gilvifrons (Mulsant) (Coleoptera: Coccinellidae) and Nabis viridulus Spinola (Hemiptera: Nabidae). Franzman (2002) reported that H. variegata is the most important natural enemy of aphids, whiteflies, mealybugs, lepidopteran and coleopteran insects in many countries. It is known that this species feeds on eggs and first instars of Ostrinia nubilalis (Kayapınar & Kornoşor, 1993), Pieris rapae L. (Schmaedıck & Shelton, 2000) and S. exigua (Atlıhan et al, 2003).…”
Section: Agrius Convolvuli (L) (Sphingidae)mentioning
confidence: 99%